Who Benefits from Guidance Counseling? Insights into Native and Immigrant Students of Low Social Origin - Irena Pietrzyk; Marita Jacob; Melinda Erdmann (KZfSS Kölner Zeitschrift für Soziologie und Sozialpsychologie, 2023)
Research on educational inequalities has increasingly focused on interventions to increase enrollment in higher education for students of low social origin. However, students of low social origin may not be homogeneous in their need for advice, as natives of low social origin decide less frequently to enter university than their immigrant counterparts in many European countries. Drawing on data from a~randomized controlled trial in German schools, we find that counseling in particular does indeed increase the likelihood of enrollment for native students. We then use the results of our empirical analyses to illustrate how an upscaling across schools would affect migration-specific enrollment rates of students of low social origin at the aggregate level. We discuss the implications of our results for research on migration-related inequalities in enrollment as well as for policy regarding program upscaling.
Keywords: 300; Higher education; Educational inequality; Social origin; Immigrant background; Randomized controlled trial; Studium; Bildungsungleichheit; Soziale Herkunft; Migrationshintergrund; Randomisiert kontrollierte Studie